Adalimumab for the treatment of non-infectious uveitis: an updated review. (1st February 2017) - Kubaisi, Buraa; Syeda, Sarah; Schmidt, Alexander; Foster, C. Stephen
ABSTRACT: Introduction : The recent approval of adalimumab (trade name Humira, Abbvie inc.) by the FDA for the treatment of noninfectious intermediate, posterior and panuveitis marks the first 'on label' non-corticosteroid drug available to ophthalmologists. Immunomodulatory (IMT) and biologic agents have long been shown to be effective in inducing remission of chronic uveitis but have remained as orphan drugs due to lack of financial incentive and perceived need. Areas c overed : Here we provide detail into the background and use of adalimumab for uveitic patients. Topics include pharmacology, therapeutic indications and usage, dosage, drug safety, physician monitoring, side effects and adverse events. Expert o pinion : We see the approval of adalimumab for uveitis as an important milestone improving upon the accepted standards of care for patients with this severe, sight threatening disease. We implore medical professionals to consider the use of IMT and biologic treatments for patients with recurrent non-infectious uveitis, referring to ocular immunology and uveitis specialists when necessary.